Enhancing Zero Trust Architecture with AI-Driven Threat Intelligence in Cloud Environments - Sairaj Kommera, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the integration of Artificial Intelligence (AI) with Zero Trust Architecture (ZTA) in cloud environments, presenting a comprehensive framework for enhancing cybersecurity in modern digital ecosystems. It begins by examining the core principles of Zero Trust Architecture, including micro-segmentation, identity-based access controls, and continuous verification. The role of AI in cybersecurity is then discussed, focusing on its capabilities in analyzing large-scale datasets, identifying anomalous behaviors, and predictive threat detection. The synergy between AI and ZTA is explored in depth, highlighting how this combination enables real-time threat analysis, advanced behavior pattern recognition, and improved threat intelligence parsing. A case study illustrates the practical implementation of AI-enhanced ZTA, demonstrating significant improvements in threat detection, response times, and overall security posture. The article also addresses key challenges and considerations, including AI bias, resource requirements, and data governance issues. Finally, it provides a roadmap for organizations looking to implement AI-enhanced ZTA, covering assessment, tool selection, performance optimization, and regulatory compliance. This comprehensive exploration offers valuable insights for security professionals and researchers, bridging the gap between theoretical advancements and practical applications in the rapidly evolving field of cybersecurity.
Keywords: Zero Trust Architecture (ZTA); Artificial Intelligence in Cybersecurity; AI-Enhanced Threat Intelligence; Micro-segmentation; Continuous Verification